“This Graft-vs.-Host Disease Determines My Life. That's It.”—A Qualitative Analysis of the Experiences and Needs of Allogenic Hematopoietic Stem Cells Transplantation Survivors in Germany - Parisek, Mira; Loss, Julika; Holler, Ernst; Barata, Anna; Weber, Daniela; Edinger, Matthias; Wolff, Daniel; Schoemans, Helene; Herrmann, Anne (Frontiers in Public Health, 2021)
Background: Allogeneic hematopoietic stem cell transplantation (alloHSCT) is the only curative treatment modality for many patients affected by hematologic malignancies. However, it can cause debilitating long-term effects. Understanding the impact of alloHSCT on all aspects of the patients' life is required for optimal survivorship management. Aim: To explore in-depth HSCT-survivors' experiences and needs post-transplant. Partners were included to provide further information on survivors' needs and how care could be improved in this area. Methods: We conducted semi-structured face-to-face and phone interviews with alloHSCT-survivors and their partners referred to a survivorship clinic in Germany. Theoretical sampling was used to recruit participants. Data were analyzed using framework analysis. Results: Thirty-two survivors (consent rate: 100%, response rate: 100%) and eighteen partners (consent rate: 84%, response rate: 72%) participated. Survivors were aged between 25 and 68 years (Median: 48, IQR: 25.3) and partners were aged between 26 and 64 years (Median: 54, IQR: 16, SD: 12.8). The themes emerging from the data involved survivors' needs included (i) the diversity of long-term treatment side-effects; and (ii) time post discharge as a dynamic process with individual peaks of burden. Survivors and their partners also suggested strategies for mitigating these unmet needs, i.e., (iii) transparent communication and patient empowerment; and (iv) improvement in continuity of care system and help with claiming social benefits as cornerstones of optimal survivorship care. Conclusion: To our knowledge, this is one of the first qualitative studies focused on the views of German alloHSCT-survivors on the long-term effects of alloHSCT and the first study integrating the view of their partners. Healthcare providers could better support survivors with managing their symptoms and adhering to their prescribed care by ensuring comprehensive, transparent communication that helps increase survivors' understanding and involvement in their care. Further efforts should be made to provide patient-centered, continuous survivorship care that involves additional support with navigating the healthcare and social service system. Intervention studies are required to test the effectiveness of the suggested strategies.